2017
DOI: 10.1080/02701367.2017.1402114
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Peer Teaching for Learning Games: An Action Research Intervention Across Three Consecutive Sport Education Seasons

Abstract: While sport education has the capacity to develop competent players, different levels of teacher guidance and learners' instructional responsibility are necessary when teaching tactics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
2
14
0
9
Order By: Relevance
“…At that point in the learning process, although direct instruction and behavioural modelling benefited players' decision-making ('what to do'), this approach did not favour players' skillexecution ('how to do'), nor their ability to autonomously respond to the variability of game circumstances. This is in keeping with the findings by Farias et al (2018), where the teacher-led identification of the teams' game-play problems and proposition of solutions in early stages of games learning led to students' higher engagement in game-play. Despite the 'setback' in terms of students' short-term playing ability, Farias et al (2018) stressed the use of guidance-based strategies was a necessary procedure for shaping effective instructional interactions managed by the student-coaches during the peer-teaching dynamics.…”
Section: Instruction Content Development Cognitive and Situated Desupporting
confidence: 87%
See 2 more Smart Citations
“…At that point in the learning process, although direct instruction and behavioural modelling benefited players' decision-making ('what to do'), this approach did not favour players' skillexecution ('how to do'), nor their ability to autonomously respond to the variability of game circumstances. This is in keeping with the findings by Farias et al (2018), where the teacher-led identification of the teams' game-play problems and proposition of solutions in early stages of games learning led to students' higher engagement in game-play. Despite the 'setback' in terms of students' short-term playing ability, Farias et al (2018) stressed the use of guidance-based strategies was a necessary procedure for shaping effective instructional interactions managed by the student-coaches during the peer-teaching dynamics.…”
Section: Instruction Content Development Cognitive and Situated Desupporting
confidence: 87%
“…Two examples of the generated categories were 'two-goals speeds up transition and game pacing' and 'tactical questioning helps reading/playing the game better'. As proposed by Sparkes and Smith (2014), several procedures were employed to ensure interpretative validity while minimizing the risk of individual research bias: (i) observations from the same events observed using different data sources were triangulated, (ii) the interview transcripts were presented to 'stakeholders' for checking for accuracy of the interpretation of meanings and intentions implicit in their words, and, (iii) the data was collaboratively scrutinised by the first author and his co-authors who acted as 'critical friends' within the interpretational analysis (see Farias et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspects such as the study of predominant configurations of players' gameplay and similar tactical principles across games within the same category prevented a setback in the complexity of the learning content addressed at the beginning of each season. Players also showed an increasing ability to adapt gameplay to game conditions (13).…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, teachers play a key facilitative role whereby they mediate team selection of appropriate practice tasks and encourage student engagement in debates-of-ideas (Gréhaigne et al, 2010). The ultimate goal is the development of learners' progressive ability to devise appropriate strategies and plans of action to successfully solve their teams' game problems (Farias et al, 2018).…”
Section: Student-centred Approaches To Teaching and Learning Of Sportmentioning
confidence: 99%